The purposes of Islamic sharia politics - Haroush, Ayman Mohammed (Journal of Islamic Sciences, 2021)
In this research a study of the goals of Islamic politics. He talked about the concept of the objectives and their types, and concept of legal politics, then he separated the objectives sought by the street from the jurisprudence of Sharia policy, the researcher wanted to clarify the objectives of politics and highlight the purpose of its jurisprudence, and to show the beauty and merits of the law in this regard, and correct the course of political action to comply with the legitimate objectives. The research was conducted after extrapolating the texts of Sharia and the words of the jurists on the topic of Sharia policy, the legal policy was generally intended to preserve the worldly interests of the people, such as achieving security, services and civilized development, and eschatological interests, such as preserving religion and spreading moral values and science. The research recommended teaching the purposes of Sharia policy to researchers and those working in politics, and need to activate political jurisprudence in contemporary calamities according to the purposes of political law.